2018
DOI: 10.1002/ajhb.23100
|View full text |Cite
|
Sign up to set email alerts
|

Ancient and recent Middle Eastern maternal genetic contribution to North Africa as viewed by mtDNA diversity in Tunisian Arab populations

Abstract: The Middle Eastern maternal genetic contribution to Tunisian populations, as to other North African populations, occurred mostly in deep prehistory. They were brought in different migration waves during the Upper Paleolithic, probably with the expansion of Iberomaurusian culture, and during Epipaleolithic and Early Neolithic periods, which are concomitant with the Capsian civilization. Middle Eastern lineages also came to Tunisia during the recent Islamic expansion of the 7th CE and the subsequent massive Bedo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 106 publications
2
11
0
Order By: Relevance
“…2). This result reinforces the differentiation between these two populations previously documented through the analysis of the maternal diversity revealing that Wesletia exhibited a rate of Middle Eastern mtDNA lineages (28.1%) larger than Kairouan (12%) 38 .…”
Section: Figure 3 Median-joining Network Of Haplogroup T Based On 17 Y-str (A) and 13 Y-str (B) In Northsupporting
confidence: 90%
See 2 more Smart Citations
“…2). This result reinforces the differentiation between these two populations previously documented through the analysis of the maternal diversity revealing that Wesletia exhibited a rate of Middle Eastern mtDNA lineages (28.1%) larger than Kairouan (12%) 38 .…”
Section: Figure 3 Median-joining Network Of Haplogroup T Based On 17 Y-str (A) and 13 Y-str (B) In Northsupporting
confidence: 90%
“…Influences from the Middle East in the region of Wesletia left marks in the remains of prehistoric human occupation of the region, at least from Neolithic times on, in many refuges of Jebel Ousselat such as Ain Khanfous, Chendoube, Knefissa, Oued Grabech and Oued Bourrime, where abound rock paintings of domestic animals and hunting scenes 4,5 . Also the study of Fadhlaoui-Zid et al 15 sustained this scenario, estimating the coalescence age of J-M267 in Cosmopolitans from Sousse at 7.6 ± 5.2 kya; as well the recent phylogenetic analysis of Middle Eastern mtDNA lineages 38,66 argues in favour of the eastern gene flow to North Africa during Neolithic periods as part of the Capsian civilization development. Notably for the mtDNA R0a and T1a haplotypes found in the Tunisian sample from Wesletia examined in this study, the TMRCAs were estimated around 9000 to 5000 ya 38 .…”
Section: Figure 3 Median-joining Network Of Haplogroup T Based On 17 Y-str (A) and 13 Y-str (B) In Northmentioning
confidence: 89%
See 1 more Smart Citation
“…Although a clear‐cut differentiation can also be appreciated for the European component, more frequent among Berbers than Arabs, this was found at a lower frequency than the other two mentioned previously. Sub‐Saharan and Near Eastern ancestries, which are known to have been brought to North Africa through a variety of ancient (pre‐neolithic and neolithic) and recent (Arab conquest) migratory waves (Newman, 1995; Appiah & Gates, 2010; Henn et al, 2012; van de Loosdrecht et al, 2018; Fregel et al, 2018; Elkamel, Boussetta, Khodjet‐El‐Khil, Benammar Elgaaied, & Cherni, 2018; D'Atanasio et al, 2018), were found not to vary substantially among the Southern Tunisia ethno‐linguistic groups.…”
Section: Discussionmentioning
confidence: 99%
“…While Tunisian populations are known to be characterized by the remarkable cultural diversity outlined above, the structure of their genetic variation studies has yet to be exhaustively investigated. Most of the studies conducted so far have used unilinear polymorphisms, which may help trace specific demographic events but cannot investigate the genetic structure in all its aspects (Cherni et al, 2009;Elkamel et al 2018;Ennafaa et al, 2011;Fadhlaoui-Zid et al, 2004;Frigi, Cherni, Fadhlaoui-Zid & Benammar-Elgaaied, 2010;Frigi et al, 2017;Loueslati et al, 2006;Kefi et al, 2015). Furthermore, genomic approaches, which can define the relationships among individuals and groups more comprehensively, have been limited to Berbers (Arauna et al, 2017;Henn et al, 2012).…”
Section: Introductionmentioning
confidence: 99%